Compact disks, a new source for gold electrodes. Application to the quantification of copper by PSA - Richter, E. M.; Augelli, M. A.; Magarotto, S.; Angnes, L. (Wiley-Blackwell, 2001)
In this work we describe a versatile and very sensitive way for copper quantification by potentiometric stripping analysis using gold electrodes obtained from recordable compact disks (CDs). This new source of electrodes (CDtrodes) shown similar performance to the commercial gold electrodes with superior versatility and lower cost. Recordable CDs contains a highly pure gold film with thickness between 50 and 100 nm and superficial area of ca. 100 cm(2). The working electrode developed was used successfully in stationary cell and many experimental parameters have been optimized. For copper, the detection limit attained was 30 ng L-1 (600 s deposition time) with remarkable precision (standard deviation of 1.8 % for 20 repetitive measurements using 25 mu gL(-1) of copper with 60 s of deposition time). The gold electrode developed was used for analysis of copper in sugar cane spirits and tap water samples. The results were compared with those obtained by atomic absorption spectroscopy.
Keywords: gold electrodes; CD electrodes; copper; sugar cane spirits; beverages; tap water; potentiometric stripping analysis